Will McGugan on Text-Based User Interfaces - Kapfhammer, Gregory; Blumen, Robert; Vaidhyanathan, Karthik (IEEE software, 2025)
In episode 669 of Software Engineering Radio, Will McGugan, the CEO and founder of Textualize, speaks with host Gregory M. Kapfhammer about how to use packages such as Rich and Textual to build text-based user interfaces (TUIs) and command-line interfaces (CLIs) in Python. They discuss design idioms for building TUIs in Python, strategies for efficient rendering, and the challenges of creating performant frameworks like Textual and Rich, while also outlining how developers can get started with their own CLI or TUI. We provide summary excerpts next; to hear the full interview, visit http://www.se-radio.net or access our archives via RSS at http://feeds.feedburner.com/se-radio.—Robert Blumen and Karthik Vaidhyanathan